2003
DOI: 10.4049/jimmunol.170.5.2340
|View full text |Cite
|
Sign up to set email alerts
|

Human Heat Shock Protein 60 Induces Maturation of Dendritic Cells Versus a Th1-Promoting Phenotype

Abstract: Heat shock protein (HSP) 60 nonspecifically activates cells of the innate immune system. In the present study, we characterized the effects of human HSP60 maturation, cytokine release, and T cell-activating capacity of bone marrow-derived dendritic cells (DC). Furthermore, we analyzed HSP60-induced signal transduction in DC. HSP60 strongly stimulated DC for maturation and release of TNF-α, IL-12, and IL-1β. However, HSP60 elicited only a weak IL-10 response in DC suggesting a Th1 bias. HSP60-treated DC induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
1
6

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 48 publications
1
142
1
6
Order By: Relevance
“…In this study, we also demonstrated that apoptotic tumor cells (in late phase of apoptosis) expressing HSP70 stimulate DC maturation after DC phagocytosis of these apoptotic tumor cells, which is consistent with some previous reports. [53][54][55] DCs, with phagocytosis of apoptotic tumor cells (in late phase of apoptosis) expressing HSP70 induced stronger antitumor immunity than DC with phagocytosis of tumor cells in early phase of apoptosis, which is consistent with a recent report from our group. 28 More interestingly, we demonstrated that apoptotic tumor cells expressing HSP70 in early phase of apoptosis more efficiently induce tumor-specific CTL responses and vaccine efficiency than those in late phase of apoptosis in two MCA/HSP and EG7 tumor models.…”
Section: Hsp70 Enhances Efficiency Of DC Vaccinessupporting
confidence: 92%
“…In this study, we also demonstrated that apoptotic tumor cells (in late phase of apoptosis) expressing HSP70 stimulate DC maturation after DC phagocytosis of these apoptotic tumor cells, which is consistent with some previous reports. [53][54][55] DCs, with phagocytosis of apoptotic tumor cells (in late phase of apoptosis) expressing HSP70 induced stronger antitumor immunity than DC with phagocytosis of tumor cells in early phase of apoptosis, which is consistent with a recent report from our group. 28 More interestingly, we demonstrated that apoptotic tumor cells expressing HSP70 in early phase of apoptosis more efficiently induce tumor-specific CTL responses and vaccine efficiency than those in late phase of apoptosis in two MCA/HSP and EG7 tumor models.…”
Section: Hsp70 Enhances Efficiency Of DC Vaccinessupporting
confidence: 92%
“…However, the ability of BAFF to promote Fas killing is not common to B cells activated through all TLR, since B cells activated with CpG (TLR9 ligand) show no increased susceptibility to Fas-induced death in the presence of BAFF. Additionally, we could not extend our results obtained with LPS to some other proteins (heparan sulfate and HSP60) reported as endogenous ligands of TLR-4 [35][36][37], since endotoxin-free preparations of these proteins systematically failed to activate murine B cells.…”
Section: Discussionmentioning
confidence: 66%
“…A further defect in IL2 signaling in hsf1 À/À p53 À/À mice would further amplify this defect. Furthermore, upregulation of Hsp60 expression in p53 À/À lymphomas, known to induce, at least in macrophages, secretion of cytokines such as TNFa, IL6, IL12 and nitric oxide (Flohe et al, 2003), may play a role in tumor progression providing precancerous cells with growth promoting stimuli. A greater dependence of hematological tumors (lymphomas), compared to other tumor types, on survival factors can also explain the selective suppression of lymphomas observed in our study.…”
Section: Discussionmentioning
confidence: 99%